INOVASI E-GOVERNMENT DALAM PELAYANAN PUBLIK (Studi Pada Faktor Pendukung dan Penghambat Program E-Musrenbang di Kota Surabaya) - Rahmat Rafinzar; Kismartini Kismartini (Kolaborasi : Jurnal Administrasi Publik, 2020)
E-government innovation through the implementation of e-musrenbang in the city of Surabaya has not yet provided optimal results. The problem found in this research is the lack of transparency and implementation which takes longer because the program is still done manually. The purpose of this study is to look at the implementation of the e-musrenbang system and analyze the factors that influence the implementation of e-musrenbang in the city of Surabaya. The George Edward III implementation model which includes variables that influence the implementation of policies, namely communication, resources, disposis, and bureaucratic structures. The research method used is a qualitative research method with data collection techniques through literature study. Based on the results of the study showed that the implementation of the e-musrenbang system in Surabaya City has been going well with the discovery of several supporting factors, namely sufficient human resources in the implementation process, the SOP that was followed was also very supportive. Among the obstacles to the success of the implementation of e-musrenbang are due to the gap or gap between the implementation of the system and the expectations of the community through the proposals submitted, so that the policies taken by the government in some cases are not in accordance with the needs of the community's top priorities. The process of regional development planning through e-musrenbang has become a good innovation because slowly there has been an improvement in the system of regional development planning, especially in the city of Surabaya, although there are several things that become a periodic evaluation note for the implementing committee and the community. Local governments must continue to improve the system and its implementation so that e-musrenbang can be a better public service.